2016
DOI: 10.3168/jds.2015-10396
|View full text |Cite
|
Sign up to set email alerts
|

Ryegrass pasture combined with partial total mixed ration reduces enteric methane emissions and maintains the performance of dairy cows during mid to late lactation

Abstract: The inclusion of grazed pasture in dairy feeding systems based on a total mixed ration (TMR) reduces feed costs, benefits herd health, and reduces environmental impact. The present study aimed to evaluate the effect of ryegrass pasture combined with a partial TMR on enteric methane emissions, dry matter intake (DMI), and performance of dairy cows from mid to late lactation. The experimental treatments included 100% TMR (control), partial TMR + 6h of continuous grazing (0900-1500 h), and partial TMR + 6h of gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 33 publications
3
7
0
Order By: Relevance
“…Lassey (2007) reported that ruminant livestock, across different production systems, has a typical Ym range of 4 to 10%. Recently, a relative high Ym value of 9.2%, similar to that of the current study, was reported by Dall-Orsoletta et al (2016) where dairy cows in mid to late lactation on a partial TMR were allowed to graze Italian ryegrass for short periods. Furthermore, Ym values of ruminants fed diets containing tropical grass diets (such as kikuyu) can range between 8.4 to 11.4% (Kurihara et al, 1999;Tangjitwattanachai et al, 2015), but can also be as low as 4.9% (Noguera and Posada, 2017).…”
Section: Itemsupporting
confidence: 89%
“…Lassey (2007) reported that ruminant livestock, across different production systems, has a typical Ym range of 4 to 10%. Recently, a relative high Ym value of 9.2%, similar to that of the current study, was reported by Dall-Orsoletta et al (2016) where dairy cows in mid to late lactation on a partial TMR were allowed to graze Italian ryegrass for short periods. Furthermore, Ym values of ruminants fed diets containing tropical grass diets (such as kikuyu) can range between 8.4 to 11.4% (Kurihara et al, 1999;Tangjitwattanachai et al, 2015), but can also be as low as 4.9% (Noguera and Posada, 2017).…”
Section: Itemsupporting
confidence: 89%
“…We assumed a fixed factor for the calculation of enteric CH 4 emissions but in reality, these emissions have been shown, for some breeds, to vary with feed and size. Pasture-based feed can help reduce enteric emissions [58], in particular when legumes are present [59]. Milking cows fed with legumes silage (e.g., alfalfa silage) tend to produce up to 16% less milk with up to 14% more enteric CH 4 than cows fed with concentrated feed.…”
Section: Methane Emissionsmentioning
confidence: 99%
“…Lower milk yield of cows receiving RT compared to C resulted in a lower daily yield of protein, but not fat. Milk fat concentration has previously been reported to increase (Fajardo et al, ), decrease (Dall‐Orsoletta et al, ; Morales‐Almaráz et al, ) or remain unaffected (Soriano et al, ; Vibart, Fellner, Burns, Huntington, & Green, ) when grazing was included in the diet of TMR‐fed cows. These differences may be a function of NDF intake, as pasture is typically higher in NDF than the TMR, which may be expected to increase milk fat concentration (Sutton, ).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the proportion of grazed pasture in the diet of dairy cattle can, however, offer economic, environmental, milk quality and animal welfare benefits (Hennessy, Delaby, Pol‐van Dasselaar, & Shalloo, )⁠. For example, grazing dairy cows for part of the day can lower farm expenses and increase profit in scenarios with high feed costs and low milk prices (Tozer, Bargo, & Muller, )⁠ and reduce the methane output of animals (Dall‐Orsoletta, Almeida, Carvalho, Savian, & Ribeiro‐Filho, ; Mufungwe et al, )⁠. Grazing may also increase the concentration of fatty acids (FA) in milk that are beneficial to human health (Barca et al, ; Mufungwe et al, ) and, because cows can exhibit motivation to be outside at pasture (Motupalli, Sinclair, Charlton, Bleach, & Rutter, )⁠, pasture access allows natural behaviour to be expressed which may potentially improve animal welfare.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation